Implementation of Waste Management Policy by the Environment Agency: A Case Study of Waste Transportation Equipment at the Gunung Santri Landfill, Cirebon Regency - Nur Wahidin; Fernando Hakim; Siti Khumayah; Rahmayanti Rahmayanti (Jurnal Indonesia Sosial Teknologi, 2025)
Waste management is a crucial issue in urban environmental governance, particularly concerning the effectiveness of transportation systems to final disposal sites (FDS). This study aims to examine the implementation of waste management policies by the Cirebon Regency Environmental Agency, focusing on a case study of waste transportation vehicles at the Gunung Santri FDS. The approach used is qualitative, with a case study method to deeply explore the dynamics of policy implementation in the field. The analysis is conducted using George C. Edward III’s policy implementation theory, which includes four main variables: communication, resources, implementer disposition, and bureaucratic structure. Data is collected through in-depth interviews, participatory observation, and document analysis. The research findings indicate that the implementation of waste transportation policies still faces various challenges, such as limited fleet capacity, suboptimal distribution of transportation schedules, and weak coordination among technical departments within the DLH bureaucratic structure. However, there are also improvement efforts, including updates to transportation standard operating procedures (SOPs), procurement of new fleets, and the involvement of village officials in the transportation system. The conclusion of this study emphasizes the importance of strengthening resources and cross-sector communication, as well as the need to reformulate the operational system of transportation based on regional mapping and the frequency of waste generation. This study contributes in the form of technical policy recommendations for local governments and enriches the literature on the implementation of environmental policies at the local level.